Prawn Sauce / Asnan Amdin ... [et al.] - Amdin, Asnan; Sulaiman, Amy Sulastri; Karim, Malah; Ali Hassan, Mohd Halmi; Abd Kahar, Nor Fatiah (2009)
Prawn sauce or Sambal udang ( malay language )refers to any kind of ready-to-eat fresh chili paste mixed with a variety of spices like onion, garlic and the main ingredient. The paste must have some mixture of spicy hot, sour, salty and sometimes a little sweet taste and little bit of dried prawn ( udang kering ). Our main raw material to produce is called Belacan Papar, available at Kampung Laut Papar where the best belacan in the Sabah, Malaysia. Belacan is dried shrimp paste cake. It can be eaten fresh as a dip with raw vegetables, used as a base for frying rice or cooking vegetable dishes; and added to desiccated coconut, it makes a delicious kerabu dressing like mango, kangkung and so on and ikan bakar. These ingredients are made into a paste using the old faithful pestle and mortem but nowadays we are just use a machine for to make faster and already finished, and guaranteed in quality and sanitation. Nowadays , many of people to take quite simple action to just buy food process finished in the market because there do not have many times to produce it for to serve. Furthermore, many of people like so much of belacan but there do not have finished product in the market. So, we identify this problem and then to solve this problem and our chance to excess this business. We are use bottling packaging because it is so easy to use and keep It in the refrigerator after open it, besides it is easy to enter in supermarket. For make guaranteed our product we take belacan from our supplier is Puan Fatimah in Kampung Laut Papar For increase the capacity of our production we are rent house - shop two level is our factory.